Macroscopic anisotropic bone material properties in children with severe osteogenesis imperfecta. (7th November 2017) - Albert, Carolyne; Jameson, John; Tarima, Sergey; Smith, Peter; Harris, Gerald
Abstract: Children with severe osteogenesis imperfecta (OI) typically experience numerous fractures and progressive skeletal deformities over their lifetime. Recent studies proposed finite element models to assess fracture risk and guide clinicians in determining appropriate intervention in children with OI, but lack of appropriate material property inputs remains a challenge. This study aimed to characterize macroscopic anisotropic cortical bone material properties and investigate relationships with bone density measures in children with severe OI. Specimens were obtained from tibial or femoral shafts of nine children with severe OI and five controls. The specimens were cut into beams, characterized in bending, and imaged by synchrotron radiation X-ray micro-computed tomography. Longitudinal modulus of elasticity, yield strength, and bending strength were 32–65% lower in the OI group (p < 0.001). Yield strain did not differ between groups (p ≥ 0.197). In both groups, modulus and strength were lower in the transverse direction (p ≤ 0.009), but anisotropy was less pronounced in the OI group. Intracortical vascular porosity was almost six times higher in the OI group (p < 0.001), but no differences were observed in osteocyte lacunar porosity between the groups (p = 0.086). Volumetric bone mineral density was lower in the OI group (p < 0.001), but volumetric tissue mineral density was not (p = 0.770). Longitudinal OI bone modulus and strength were correlated with volumetric bone mineral density (p ≤ 0.024) but not volumetric tissue mineral density (p ≥ 0.099). Results indicate that cortical bone in children with severe OI yields at the same strain as normal bone, and that their decreased bone material strength is associated with reduced volumetric bone mineral density. These results will enable the advancement of fracture risk assessment capability in children with severe OI.